Properties of poly (vinylidene fluoride)-co-poly (vinylimidazole) solid polymer electrolytes prepared by radiation-induced grafting method for proton exchange membrane fuel cell / Ajis Lepit - Lepit, Ajis (Institute of Graduate Studies, UiTM, 2017)
Solid polymer membranes based on graft copolymerization of 1-Vinylimidazole (VIm) onto polyvinylidene fluoride (PVDF) were synthesized. The graft copolymerization process was carried out under nitrogen atmosphere by a radiationinduced grafting (RiG) in aqueous medium. Ferrous ions were used as a redox initiator system. Radiation effects onto PVDF and VIm were investigated with the aim to develope a highly-stable grafted solid polymer membrane for potential use in proton exchange membrane fuel cells. Polymer membranes consist of PVDF as a polymer host and VIm as a monomer were prepared by solution casting technique. Prior to that, PVDF was exposed to -rays ranging from 20 to 100 kGy using RiG method to form free radicals that capable to initiate graft copolymerization of VIm onto PVDF backbone as a side chain.Various grafting conditions such as absorbtion dose, effects of different solvents and addition of Iron (II) sulfate heptahydrate were determined. Results showed that the degree of grafting (DG) was strongly influenced by the type of solvent used to dissolve the VIm. The grafted polyvinylimidazole (PVIm) onto PVDF was estimated using gravimetric analysis. DG of the VIm onto PVDF was also found to be dependent on the absorbtion dose exposed to the samples. The best absorbtion dose where the sufficent grafting occured between polymer based and monomer was at 60 kGy. Concentration of ferrous ions was observed to play a major role to initiate grafted VIm onto PVDF samples namely PVDF-co-PVIm membranes during induction of radiation. Samples were then complexed in acid sulfuric to prepare functional solid polymer electrolyte membranes as well as to enhance their ionic conductivity…